Impact of quality management system on company performance. A case of Steelmakers Zimbabwe Pvt Ltd. - Suruto, Sarah (Midlands State University, 2017)
This study was aimed at looking at the impact of QMS on company performance. The QMS which was mainly focused on was ISO 9001:2008. The background of the study unpack the key issues that drives the researcher to carry on a study on that area, which continuous decline in sales and very low customer satisfaction index. The research objectives were to determine how customer focus has an effect on customer loyalty, how leadership approach affect employee morale and the impact of continuous improvement on cost savings. Research questions were also present so as to answer the research problems. The research also highlighted the significance, limitations and delimitations of the research study. In chapter two there is the review of other related literature so as to bring the in depth understanding of the impact of Quality Management System on company performance. Exploratory and descriptive research designs were used. Out of a population of 330, 66 was drawn as the sample size which is 20%. Stratified and simple random sampling were used to draw the sample. Sample frame comprised of management, employees and customers. Research instruments used were interviews and questionnaires. Interviews were for management and questionnaire for customers and employees. Primary and secondary data sources were used also in data collection. The findings of the research were organizations might be customer focused hence no existence of customer loyalty, democratic leadership style influence positively workforce's morale and costs such as reworks and returns are greatly influenced negatively by continuous improvement strategies. The conclusion of the research revealed that leadership is the key factor which can lead to the failure of organizations which are ISO 9001:2008 certified hence there is a strong relation between QMS and company performance. The researcher also gave recommendations such as value addition training and retraining, loyalty programs, adoption of two or more leadership style, employee involvement in TQM and benchmarking against better other steel manufacturers.